Examination of the efficacy of acute L-alanyl-L-glutamine ingestion during hydration stress in endurance exercise - Yamamoto Linda M; Bailey Brooke L; Anderson Steven; Stec Michael; Gonzalez Adam M; Kelly Neil; Rashti Stephanie L; Kang Jie; Ratamess Nicholas A; Hoffman Jay R; Hom Lindsay L; Kupchak Brian R; et al. (Taylor & Francis Group, 2010)
Abstract Background The effect of acute L-alanyl-L-glutamine (AG; Sustamine™) ingestion on performance changes and markers of fluid regulation, immune, inflammatory, oxidative stress, and recovery was examined in response to exhaustive endurance exercise, during and in the absence of dehydration. Methods Ten physically active males (20.8 ± 0.6 y; 176.8 ± 7.2 cm; 77.4 ± 10.5 kg; 12.3 ± 4.6% body fat) volunteered to participate in this study. During the first visit (T1) subjects reported to the laboratory in a euhydrated state to provide a baseline (BL) blood draw and perform a maximal exercise test. In the four subsequent randomly ordered trials, subjects dehydrated to -2.5% of their baseline body mass. For T2, subjects achieved their goal weight and were not rehydrated. During T3 - T5, subjects reached their goal weight and then rehydrated to 1.5% of their baseline body mass by drinking either water (T3) or two different doses (T4 and T5) of the AG supplement (0.05 g·kg-1 and 0.2 g·kg-1, respectively). Subjects then exercised at a workload that elicited 75% of their VO2 max on a cycle ergometer. During T2 - T5 blood draws occurred once goal body mass was achieved (DHY), immediately prior to the exercise stress (RHY), and immediately following the exercise protocol (IP). Resting 24 hour (24P) blood samples were also obtained. Blood samples were analyzed for glutamine, potassium, sodium, aldosterone, arginine vasopressin (AVP), C-reactive protein (CRP), interleukin-6 (IL-6), malondialdehyde (MDA), testosterone, cortisol, ACTH, growth hormone and creatine kinase. Statistical evaluation of performance, hormonal and biochemical changes was accomplished using a repeated measures analysis of variance. Results Glutamine concentrations for T5 were significantly higher at RHY and IP than T2 - T4. When examining performance changes (difference between T2 - T5 and T1), significantly greater times to exhaustion occurred during T4 (130.2 ± 340.2 sec) and T5 (157.4 ± 263.1 sec) compared to T2 (455.6 ± 245.0 sec). Plasma sodium concentrations were greater (p < 0.05) at RHY and IP for T2 than all other trials. Aldosterone concentrations at RHY and IP were significantly lower than that at BL and DHY. AVP was significantly elevated at DHY, RHY and IP compared to BL measures. No significant differences were observed between trials in CRP, IL-6, MDA, or in any of the other hormonal or biochemical measures. Conclusion Results demonstrate that AG supplementation provided a significant ergogenic benefit by increasing time to exhaustion during a mild hydration stress. This ergogenic effect was likely mediated by an enhanced fluid and electrolyte uptake.